Edukasi Pemanfaatan Daun Kecipir (Psophocarpus tetragonolobus L.) sebagai Antihiperkolesterolemia di Rumah Sakit Sembiring - Sianipar, Masria Phetheresia; Gultom, Evi Depiana; Barus, Lidia Klorida; Sembiring, Tio Ranti Sari (INSTITUT KESEHATAN DELI HUSADA, 2025)
Hypercholesterolemia is one of the leading risk factors for cardiovascular disease, with increasing global preval_ence. The use of medicinal plants as complementary therapy offers a promising alternative, one of which is winged bean leaves (Psophocarpus tetragonolobus L.), known for their flavonoid and antioxidant content. This community service activity aimed to educate the public on the potential benefits of winged bean leaves in managing high cholesterol levels. The method involved health education sessions, interactive discussions, and leaflet distribution to patients and their families at Sembiring Hospital. Results showed a 73.5% increase in participants' knowledge after the educational intervention. Education on the use of herbal remedies such as winged bean leaves plays an important role in promoting natural and accessible approaches to hypercholesterolemia prevention and management.